Outcome of Pregnancy in Booked Vs Un-Booked Patients - Kanwal, Iqra; Javed, Naureen; Murtaza, Adnan; Mustafa, Zeeshan; Iqbal, Sana; Khan, Shehreen (Indus Journal of Bioscience Research, 2025)
Objective: To determine the outcome of pregnancy in booked vs un-booked patients. Study Design: Comparative, cross sectional. Place and Duration of Study: Department of Obstetrics and Gynecology, Allied Hospital, Faisalabad. From 1st January 2025 to 31st March 2025. Methodology: Total 570 primigravida or multigravida of 18-40 years of age and both booked and un-booked. Women with known gestational diabetes mellitus, renal, liver, and heart conditions, as well as anemia (Hb<11g/dl), were not included. Patients were divided into two groups as per their booking status. Booked Patients were kept in group A and unbooked patients were kept in group B. Patients in both the groups were followed till delivery and outcome was noted in terms of preterm birth, emergency caesarean section, Intrauterine Death or Neonatal Death). Results: 20 patients (7.02%) in Group A delivered preterm, 17 patients (5.96%) had emergency cesarean section, 11 patients (3.86%) had intrauterine death, and there were 05 (1.76%) documented neonatal death. Group B, on the other hand, had adverse outcome: 53 patients (18.60%) reported preterm birth, 34 (11.93%) had emergency cesarean section, and 29 (10.18%) had intrauterine death. In Group B, 13 patients (4.56%) had neonatal death. We provide the p-values for preterm birth (p=0.0001), emergency cesarean section (p=0.0126), intrauterine death (p=0.0032) and neonatal death (p=0.0462). Conclusion: This study concluded that women who are unbooked throughout pregnancy have higher negative pregnancy outcomes.